Local Electric Field Promoted Kinetics and Interfacial Stability of a Phosphorus Anode with Ionic Covalent Organic Frameworks (Adv. Mater. 3/2023). Issue 3 (19th January 2023) - Cao, Yu; Zhang, Shaojie; Zhang, Baoshan; Han, Chengyu; Zhang, Yiming; Wang, Xiaoyi; Liu, Shuo; Gong, Haochen; Liu, Xinyi; Fang, Siyu; Pan, Fusheng; Sun, Jie
Abstract : Local Electric Field In article number 2208514, Jie Sun and co‐workers report the development of a local electric field by constructing ionic covalent organic frameworks to comprehensively solve the problems of the phosphorus anode. These multifunctional facets are mainly embodied in inhibiting the dissolution of intermediates, promoting the reaction kinetics, and regulating the solid electrolyte interphase, and the obtained phosporus anode demonstrates favorable performance for lithium‐ion batteries.